Designing Tools to Increase Productivity and Efficiency in the Agricultural Sector by Paying Attention to User Needs and Product Design - Herfaida Nadia Ningrum; Sri Martini; Ilma Mufidah (Ridwan Institute, 2023)
The agricultural sector is one of the important sectors that can improve the industrial economy of a country. Indonesia is a country with a high level of agricultural sector. One important aspect that needs to be considered in the agricultural sector to increase the country's income is the level of welfare of agricultural actors themselves. This welfare can be in the form of adequate agricultural tools that can streamline the flow and processes in their business. With the development of time and modernization changes, the agricultural sector is the most impacted sector in industrialization. Farmers must strive to understand technological changes that make it difficult for them to use modern agricultural tools. This research intends to innovate traditional tools such as shovels and forks called the Multifunctional Folding Shovel with product specifications including (1) hinges that rotate 90', and (2) product prices that are less than Rp. 90,000, (3) the product has a brown color, (4) the height of the product is following the average Indonesian, (5) iron that does not rust easily, (6) rubber that is not slippery, (7) product that can be folded, and (8) iron that does not get hot easily. The main purpose of this innovation development is diverse, namely to increase the effectiveness and efficiency of shovels and forks, and to facilitate farmers in carrying out their business processes without having to think about their limited ability to use technology.